2021
DOI: 10.1093/biosci/biab020
|View full text |Cite
|
Sign up to set email alerts
|

Provoking a Cultural Shift in Data Quality

Abstract: Ecological studies require quality data to describe the nature of ecological processes and to advance understanding of ecosystem change. Increasing access to big data has magnified both the burden and the complexity of ensuring quality data. The costs of errors in ecology include low use of data, increased time spent cleaning data, and poor reproducibility that can result in a misunderstanding of ecosystem processes and dynamics, all of which can erode the efficacy of and trust in ecological research. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…This analysis found that 13% of the days with rainfall and 7% of the runoff events sampled had errors indicating that the prior or existing QAQC protocols are relatively robust. However, considering the widespread use of WGEW data and the substantial investment in data collection, continued investment to improve and develop measurement protocols and QAQC procedures are warranted, e.g., [62].…”
Section: Discussionmentioning
confidence: 99%
“…This analysis found that 13% of the days with rainfall and 7% of the runoff events sampled had errors indicating that the prior or existing QAQC protocols are relatively robust. However, considering the widespread use of WGEW data and the substantial investment in data collection, continued investment to improve and develop measurement protocols and QAQC procedures are warranted, e.g., [62].…”
Section: Discussionmentioning
confidence: 99%
“…Decision-support framework Shafer et al (2000); Schultz et al (2015) Integrated workflows among teams and operational processes Abeysirigunawardena et al (2015); Hudson et al (1999);McCord et al (2021); Shafer et al (2000) Proper sensor procurement, configuration and routine calibration traceable to applicable standards Assessments and audits against performance targets Hudson et al (1999); Schultz et al (2015)…”
Section: Literature Referencementioning
confidence: 99%
“…Yet, there is comparatively very little scientific literature on QMS frameworks for sensor networks and how they are applied effectively and efficiently at the network scale (although some examples exist, e.g. Fiebrich et al, 2010; McCord et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Big data is becoming a vital resource to address unique customer requirements and gain competitive advantages. The development of big data is still in the initial stage, and relevant studies focused on the definition and particular technology or solution of big data [25][26][27][28][29][30][31][32][33]. Laney [25] proposed a well-known definition of 3Vs based on the attributes of big data, including volume, velocity, and variety.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The development of big data is still in the initial stage, and relevant studies focused on the definition and particular technology or solution of big data [25][26][27][28][29][30][31][32][33]. Laney [25] proposed a well-known definition of 3Vs based on the attributes of big data, including volume, velocity, and variety. Later studies [26,27], except 3Vs, veracity, and value, were added to explain the definition of big data.…”
Section: Literature Reviewmentioning
confidence: 99%